Design Application of Augmented Reality-Based Computer Device Assembly Practicum Modules - Diah Aryani; Syahrizal Dwi Putra; Noviandi Noviandi; Habibullah Akbar (CCIT Journal, 2023)
The adaptation and use of digital technology have presented various opportunities and challenges for actors involved in educational services, i.e., colleges, educators, and students. Augmented reality has recently emerged as one of the digital technologies that have attracted the attention of many academies and practitioners; in addition, AR technology has brought about a change in the way users and machines interact that can teach and direct students to handle the topic of lessons differently and more proactively. This study aims to design and build an android-based Augmented Reality (AR) computer hardware assembly practicum module application as an alternative learning media in the computer hardware device assembly practicum module, which is expected in a learning activity to be more exciting and increase students' skills about computer assembly through AR technology can be one of the solutions to overcome the practicum module which was previously still in the form of a textbook and was not yet technology-based. The research method used is the Multimedia Development Life Cycle (MDLC), which consists of six stages, namely concept, design, material, collection, assembly, testing, and distribution. The results of the practicum module application with Augmented Reality technology can be run on mobile devices with an Android operating system for version 5.1 and above, and this module has a feature that can introduce 3-D objects of hardware devices and simulate the assembly of hardware devices 3D objects 3D IC processor components and mainboards that are driven with the touch of a finger by pairing elements (Drag and Drop).